Non-naïve organizational positivity through a generative paradox pedagogy. Issue 1 (February 2022) - Cunha, Miguel Pina e; Simpson, Ace Volkmann; Rego, Arménio; Clegg, Stewart
Positive Organizational Scholarship (POS), with positivity as a core conceptual component, is a major innovation in recent decades in management and organizational studies. Just as organization is an inherently paradox laden process, so too, we argue, is positivity. Yet in classrooms and in practice, POS is mostly taught in a manner that accepts only one side of the paradox, that which, at first glance, appears positive. Against such linear approaches we propose another possibility: teaching positivity through a pedagogy of generative paradoxes emergent from creatively harmonizing the energy of competing and interdependent positive and negative tensions. In the process we extend the notion of generative paradox as discussed in paradox literature by embracing the notion of generativity as discussed in POS theorizing where it is associated with organizational processes that facilitate outcomes of collective flourishing, abundance, wellbeing, and virtue. Our proposed three-part generative paradox pedagogy contributes to the literature on POS, organizational paradox, and management learning.